DESIGN of ASYMMETRICAL MODE of RURAL AIR ELECTRIC NETWORK 0,38/0,22 KV - Svergun U.; Miroshnyk A. (Problems of the Regional Energetics, 2010)
The method of networks schemes design is proposed for the calculation of the asymmetrical modes of air electric networks 0,38/0,22 kV and their design with the help of Electronic Workbench software.